2021
DOI: 10.1177/0957650921998228
|View full text |Cite
|
Sign up to set email alerts
|

The impact of volute aspect ratio and tilt on the performance of a mixed flow turbine

Abstract: Current trends in the automotive industry towards engine downsizing means turbocharging now plays a vital role in engine performance. The purpose of turbocharging is to increase the engine inlet air density by utilising, the otherwise wasted energy in the exhaust gas. This energy extraction is commonly accomplished through the use of a radial turbine. Although less commonly used, mixed flow turbines can offer aerodynamic advantages due to the manipulation of blade leading (LE) angles, improving performance at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…But at 180°and 210°, the secondary flows in Case 1 volute become weaker than that in the baseline volute. This is consistent with the results in Cerdoun and Ghenaiet 11 and Lee et al 13,14 Because of the increasing influence from the discharging flows, the secondary flows in volute with narrow cross-sections disappear quickly at large azimuthal angles. The baseline volute has the strongest secondary flows at 180°and 210°, this is mainly because its circular cross-sectional shape.…”
Section: Impacts Of Volute Cross-sectional Shapessupporting
confidence: 92%
“…But at 180°and 210°, the secondary flows in Case 1 volute become weaker than that in the baseline volute. This is consistent with the results in Cerdoun and Ghenaiet 11 and Lee et al 13,14 Because of the increasing influence from the discharging flows, the secondary flows in volute with narrow cross-sections disappear quickly at large azimuthal angles. The baseline volute has the strongest secondary flows at 180°and 210°, this is mainly because its circular cross-sectional shape.…”
Section: Impacts Of Volute Cross-sectional Shapessupporting
confidence: 92%
“…Hamel et al [4] investigated a twin entry flow turbine volute. In papers [5][6][7] presented the aerodynamic performance of the mixed flow turbine blade design. Bencherif et al [8] studied the unsteady performance of a twin-entry mixed flow turbine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dean vortices, which were first reported by Dean, 9,10 have been found in the turbine volutes. 1113 The Dean vortices are caused by an imbalance between centrifugal force and the radial pressure gradient. Cerdoun and Ghenaiet 11 conducted a numerical study to characterize the flow of a twin entry radial turbine and the development of Dean vortices in its asymmetrical volute.…”
Section: Introductionmentioning
confidence: 99%
“…They modified the volute by increasing the A/R of the hub side volute and decreasing the A/R of the shroud side volute, and then the Dean vortices disappeared in the modified volute. Lee et al 12,13 studied the impact of volute aspect ratio and tilt on the performance of a mixed flow turbine. Their results showed that the aspect ratio of the volute has a significant effect on the development of the secondary flow within the volute.…”
Section: Introductionmentioning
confidence: 99%